Comment on Passfield et al: validity of the training-load concept - McLaren, S. J.; Shushan, T.; Schneider, C.; Ward, P. (International Journal of Sports Physiology and Performance, 2022)
Comment to Passfield et al: validity of the training-load concept (SPONET ID 4078178): A recent review by Passfield et al critiqued the validity of the training load concept. They raise several interesting issues, many of which we agree with and have previously voiced. However, we contend that they did not criticize the concept of training load, as reported in their title and affirmed in various sentences of the article, but rather the metrics used to quantify training load. Training load is a higher-order, multidimensional construct that is not directly measurable but can be quantified in various ways according to how it is operationalized. For this reason, there can be no single "gold standard" criterion measure. Training load is the amount of physical training done or experienced by athletes. Internal and external training load are subdimensions of training load—each also a multidimensional construct—and can be operationalized to permit the use of measures as indicators of the construct(s). Questioning training load as a construct would require questioning its conceptualization, not the measures (operationalization of the construct).